Maximum likelihood estimation and lagrange multiplier tests for panel seemingly unrelated regressions with spatial lag and spatial errors: An application to hedonic housing prices in Paris - Badi H. Baltagi; Georges Bresson (Institute for the Study of Labor (IZA), 2010)
This paper proposes maximum likelihood estimators for panel seemingly unrelated regressions with both spatial lag and spatial error components. We study the general case where spatial effects are incorporated via spatial errors terms and via a spatial lag dependent variable and where the heterogeneity in the panel is incorporated via an error component specification. We generalize the approach of Wang and Kockelman (2007) and propose joint and conditional Lagrange Multiplier tests for spatial autocorrelation and random effects for this spatial SUR panel model. The small sample performance of the proposed estimators and tests are examined using Monte Carlo experiments. An empirical application to hedonic housing prices in Paris illustrates these methods. The proposed specification uses a system of three SUR equations corresponding to three types of flats within 80 districts of Paris over the period 1990-2003. We test for spatial effects and heterogeneity and find reasonable estimates of the shadow prices for housing characteristics.
Keywords: C31; C33; R21; 330; hedonic housing prices; Lagrange multiplier tests; maximum likelihood; panel spatial dependence; spatial lag; spatial error; SUR; Maximum-Likelihood-Methode; Panel; Statistischer Test; Immobilienpreis; Hedonischer Preisindex; Wohnstandort; Theorie; Schätzung; Paris